Sensation seeking, Work Motivation, Job Satisfaction and Marital consent in female teachers - Asadzadeh, Hassan (International Journal of Education and Cognitive Sciences, 2022)
Introduction: The present study aims was to examine the relationship between sensation seeking, happiness with marital satisfaction in female teachers of high school in Ahwaz. Materials and method: In doing so, 260teachers from the education office of 4 districts Ahvaz were selected using random sampling. The sample responded to the Sensation Seeking Scale (Zuckerman, 1987), Work Motivation and Job Satisfaction Scale (Akinboye’s, 2001) and Satisfaction Marital Questionnaire (Olson, et al., 1987). Data analysis involved both descriptive and inferential statistics including mean, standard deviation, Pearson’s correlation coefficient and regression analysis.Results: Sensation seeking, Motivation and Job Satisfaction showed significant correlation with marital satisfaction. Results of multi regression analysis also revealed that overall, sensation seeking; Motivation and Job Satisfaction can predict 0.29 changes of marital satisfaction.Conclusion: Job satisfaction and Work Motivation and Marital satisfaction helps people to be successful cheerful and likely to experience a fulfilling life and manage sensation seeking which motivated to continuously work for things that will make them happy and experience new emotions.